2008
DOI: 10.1073/pnas.0804825105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rab27 in synaptic transmission at the squid giant synapse

Abstract: Small GTPase Rab is a member of a large family of Ras-related proteins, highly conserved in eukaryotic cells, and thought to regulate specific type(s) and/or specific step(s) in intracellular membrane trafficking. Given our interest in synaptic transmission, we addressed the possibility that Rab27 (a close isoform of Rab3) could be involved in cytosolic synaptic vesicle mobilization. Indeed, preterminal injection of a specific antibody against squid Rab27 (anti-sqRab27 antibody) combined with confocal microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…These findings complement recent observations in invertebrate systems, where recycling defects were noted following genetic ablation or antibody-induced depletion of Rab27 proteins (Mahoney et al, 2006;Yu et al, 2008). Interestingly, we found that both GTP-and GDP-preferring Rab27b mutants profoundly impair stimulus-dependent recycling of SVs.…”
Section: Rab27b Regulates the Recycling Of Svssupporting
confidence: 66%
See 2 more Smart Citations
“…These findings complement recent observations in invertebrate systems, where recycling defects were noted following genetic ablation or antibody-induced depletion of Rab27 proteins (Mahoney et al, 2006;Yu et al, 2008). Interestingly, we found that both GTP-and GDP-preferring Rab27b mutants profoundly impair stimulus-dependent recycling of SVs.…”
Section: Rab27b Regulates the Recycling Of Svssupporting
confidence: 66%
“…sion in invertebrates (Mahoney et al, 2006;Yu et al, 2008); but their precise subcellular localization has been unclear. In the following experiments, we have compared the subcellular localization of Rab27b with that of Rab3a using complementary approaches to determine whether they reside on identical or different synaptic vesicle pools.…”
Section: Rab3a and Rab27b Reside On Distinct Yet Overlapping Sv Poolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This synergy was not unexpected given the recent attention focused on Rab27 in SV docking and release in invertebrate systems. 28,29 Interestingly, we found that along with its inhibitory effect on uptake of a dye marker for endocytosis, dominantnegative Rab27b overexpression correlated with a depletion of endogenous Rab3a. As Rab3/Rab27b proteins share evolutionary conserved GTP-exchange factors i.e., Rab3GEF 28,30 together with the knowledge that GDP-mutants sequester cognate RabGEFs, 31 we reasoned that the GDPpreferring Rab27b mutants compete out Rab3a activation, thus accounting for the more pronounced SV recycling defect.…”
Section: Rab3a and Rab27b: Working Together To Safe-guard Synaptic Trmentioning
confidence: 89%
“…Because treatment of parotid acinar cells with EPI64 antisense LNA significantly reduced the amount of amylase released, cytosolic EPI64 increase after IPR stimulation is also likely to regulate the biogenesis and/or recycling of secretory granules (e.g. transport of secretory granules to the apical region), in which Rab27 may be involved (42,43). A proper GTP-GDP cycle of Rab27 is presumably required for these processes.…”
Section: Discussionmentioning
confidence: 99%